2017
DOI: 10.1590/0103-8478cr20161073
|View full text |Cite
|
Sign up to set email alerts
|

Indicators to assess goat welfare on-farm in the semiarid region of Brazilian Northeast

Abstract: In 2015, AWIN Goat Protocol was published in Europe, with indicators that identify welfare level of lactating dairy goats; however, there are no welfare protocols for meat goat. Therefore, the objective of this study was to select animal and resource-based indicators to assess welfare in meat goat in different types of grazing systems in Brazilian semiarid Northeast. Eighteen indicators were selected to evaluate the welfare of meat goat. The knowledge of the welfare degree of these animals is the best way to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…According to Alam et al [ 24 ], indigenous goats exposed to zero, four and eight hours of heat stress showed a significant difference in their rectal temperatures. Further, similar findings occurred in Osmanabadi, Malabari and Salem Black goat breeds of southern India [ 21 ], Barbari goats of Northern India [ 33 ], and Brown-Pardo-Sertaneja, Azul, Graúna and Moxotó breeds of Brazil [ 50 , 51 , 52 , 53 ].…”
Section: Physiological Mechanisms Of Goats Towards Adaptation or Reaction To Heat Stresssupporting
confidence: 63%
“…According to Alam et al [ 24 ], indigenous goats exposed to zero, four and eight hours of heat stress showed a significant difference in their rectal temperatures. Further, similar findings occurred in Osmanabadi, Malabari and Salem Black goat breeds of southern India [ 21 ], Barbari goats of Northern India [ 33 ], and Brown-Pardo-Sertaneja, Azul, Graúna and Moxotó breeds of Brazil [ 50 , 51 , 52 , 53 ].…”
Section: Physiological Mechanisms Of Goats Towards Adaptation or Reaction To Heat Stresssupporting
confidence: 63%
“…pdf> for goats, or <https://air.unimi.it/ bitstream/2434/269114/2/AWINProtocolSheep.pdf> for sheep). Some parameters based on the literature on goat health (CAROPRESE et al, 2009) and type and cleanliness of facilities for small ruminants in Brazilian Northeast were also added (SEBRAE, 2009;ALENCAR et al, 2010;CODEVASF, 2011;LEITE et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…AWIN Goat protocol was designed to assess the welfare of adult lactating dairy goats raised in intensive and semi-intensive systems, with a primary focus on animal-based indicators (AWIN GOAT, 2015). Although there was no specific protocol for meat goat does, the authors suggested indicators that could be used to evaluate the welfare of these animals in Brazilian Northeast (AWIN GOAT, 2015;AWIN SHEEP, 2015;LEITE et al, 2017). Therefore, the aim of the present study was to apply a protocol to evaluate the welfare of meat goat does in Brazilian Northeast farms, comparing animals kept on semi-intensive and extensive farms, quantifying the welfare problems in both groups and describing some considerations related to the protocol.…”
mentioning
confidence: 99%
“…Recently, efforts have been devoted to the development and validation of systems for the evaluation of welfare through animal-based measures, such as the European Animal Welfare Indicators (AWIN), created for sheep, goat, horses, donkeys, and turkeys [12]. Indeed, significant advances in the welfare of small ruminants have recently been achieved [13,14,15].…”
Section: Introductionmentioning
confidence: 99%